2021
DOI: 10.37859/jst.v8i1.2676
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Penyalaan Engine Sepeda Motor Berbasis Arduino Melalui Bluetooth Android

Abstract: Motorcycle ignition which also functions as a motorcycle safety needs to be designed and made as safe as possible to avoid the loss of the vehicle from theft cases. This equipment is designed to turn on/off and search for motorcycles using a remote from a smartphone with an android operating system via a bluetooth network. The bluetooth input is controlled using the Arduino Uno microcontroller. From the test results, it is found that the maximum distance that can be achieved between Android and Bluetooth to op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Bluetooth Android Andika, discussing about From the test results it was found that the maximum distance that can be achieved between Android and Bluetooth to operate a motorcycle engine is about 10 meters. This system also makes our motorcycle engine ignition a smart ignition [8].…”
Section: Research Tittle Arduino-based Motorcycle Engine Ignition Des...mentioning
confidence: 99%
“…Bluetooth Android Andika, discussing about From the test results it was found that the maximum distance that can be achieved between Android and Bluetooth to operate a motorcycle engine is about 10 meters. This system also makes our motorcycle engine ignition a smart ignition [8].…”
Section: Research Tittle Arduino-based Motorcycle Engine Ignition Des...mentioning
confidence: 99%